Carbon capture and storage - Rackley, Stephen A. (Butterworth-Heinemann/Elsevier, 2010)
Carbon dioxide capture and storage (CCS) is a technology aimed at reducing greenhouse gas emissions from burning fossil fuels during industrial and energy-related processes. CCS involves the capture, transport and long-term storage of carbon dioxide, usually in geological reservoirs deep underground that would otherwise be released to the atmosphere. Carbon dioxide capture and storage offers important possibilities for making further use of fossil fuels more compatible with climate change mitigation policies. The largest volumes of CO2 could be captured from large point sources such as from po.